Choice of playing roles of the central defenders on the basis of the analysis of the structure of the special preparedness of qualified female water polo players - Pilipko, O.; Pilipko, A. (Slobozhanskyi herald of science and sport, 2018)
Purpose: to develop and experimentally substantiate the method of choosing the game role of the central defenders on the basis of the analysis of the indicators of the structure of the special preparedness of qualified female water polo players.